Healthwallet: a digital wallet for health data privacy (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
Given the current technological scenario, increasingly present in the population's daily lives, personal data has become an extremely important asset for institutions. The use of digital identity is necessary to reduce bureaucratic processes and increase reliability in digital relationships. This work addresses a mechanism suggested by World Wide Web Consortium, the main Web standardization organization, synthesized in a data wallet, using verifiable credentials and decentralized identifiers to guarantee security, privacy and authenticity along the lines of global regulations for the public health system.
Keywords: verifiable credentials; blockchain; self-sovereign Identity; healthcare; LGPD